A preliminary discussion on STEM-drone sport’s athlete development program toward career relevance - Anies Faziehan Zakaria,; Mohd Zulfadli Rozali,; Mohd Syafiq Syazwan Mustafa, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This article aims to explore the potential for STEM education and athlete development programs to enhance career relevance in drone sports. This article provides an overview of the significance of STEM education in career development and outlines the potential for drone sports in terms of career development. This paper highlights the critical role of STEM education and athlete development programs in shaping a sustainable career path for drone sports professionals. By considering the key findings from the review, a comprehensive career relevance study can be designed and developed to support the growth of drone sports as a viable career option. This study would focus on critical skills and knowledge, including STEM education, technical proficiency, and athlete development programs. The insights gained from this article can identify and support the next generation of drone sports athletes and professionals, contributing to the growth and success of this emerging field. The ongoing study in this area has the potential to shape the development of a sustainable career path for drone sports professionals, contributing to the continued growth and popularity of this exciting field.